2004
DOI: 10.2337/diacare.27.1.141
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Glycemic Control With a Sulfonylurea Plus Pioglitazone Versus a Sulfonylurea Plus Metformin in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -The goal was to assess the 1-year efficacy and safety of the addition of pioglitazone or metformin to existing sulfonylurea (SU) therapy in patients with inadequately controlled type 2 diabetes.RESEARCH DESIGN AND METHODS -In this multicenter, double-blind study, patients were randomized to receive either pioglitazone 15 mg (n ϭ 319) or metformin 850 mg (n ϭ 320) and up to 45 mg/day and 2,550 mg/day, respectively. The primary efficacy endpoint was HbA 1c at week 52. Fasting plasma glucose, insulin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(182 citation statements)
references
References 33 publications
12
164
1
5
Order By: Relevance
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The longest treatment duration available was the 10-year follow up of metformin-treated overweight patients in the UK Prospective Diabetes Study (UKPDS). 31 Patients receiving conventional, diet-based treatment in this study gained about 2 kg over the course of the trial, with a slightly smaller weight gain of about 1.5 kg in the metformin group and of about 4 kg in the glibenclamide group (Figure 1).…”
Section: Effects Of Metformin On Body Weight In Patients With Type 2 mentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The longest treatment duration available was the 10-year follow up of metformin-treated overweight patients in the UK Prospective Diabetes Study (UKPDS). 31 Patients receiving conventional, diet-based treatment in this study gained about 2 kg over the course of the trial, with a slightly smaller weight gain of about 1.5 kg in the metformin group and of about 4 kg in the glibenclamide group (Figure 1).…”
Section: Effects Of Metformin On Body Weight In Patients With Type 2 mentioning
confidence: 99%
“…The QUARTET study randomized 639 type 2 diabetes patients suboptimally controlled on a sulphonylurea to receive double-blind treatment with additional metformin or a TZD (pioglitazone) for 1 year (Table 1b). 42 Patients receiving the resulting sulphonylurea-TZD combination gained 2.8 kg body weight, on average, compared with an average reduction of 1.0 kg in the sulphonylurea-metformin group (information of the significance of this effect was not provided). A shorter randomized study (3 months; evidence level A) showed that adding metformin to the regimens of patients suboptimally controlled on sulphonylurea resulted in smaller mean gains in weight ( þ 0.4 kg) than adding insulin lispro ( þ 3.4 kg) or NPH insulin ( þ 2.3 kg).…”
Section: Metformin and Weight A Golaymentioning
confidence: 99%
“…146 Beyond their hypoglycemic actions, PPARЎ agonists exert a number of beneficial effects in diabetes including improvement in endothelial function, 147,148 reduction in pro-atherogenic inflammatory markers 149 and angiotensin-I and -II, 150 down regulation of AT 1 mRNA and protein in vascular smooth muscle cells, 151,152 decrease in urine endothelin-1 secretion, 153 attenuated lipid accumulation and its related injury in mesangial cells, 154,155 and inhibition of glomerular and tubular cell proliferation 156,157 . Several animal [158][159][160][161][162][163] and human studies 153,[164][165][166][167][168][169][170][171][172][173][174][175] using various TZDs have demonstrated a reduction in proteinuria and BP. Unfortunately; most of these studies were of short duration averaging 1-9 months in the animal studies 158-163 and 3-12 months in human studies.…”
Section: Emerging Therapeutic Agents For Diabetic Nephropathy Thiazolmentioning
confidence: 99%
“…Unfortunately; most of these studies were of short duration averaging 1-9 months in the animal studies 158-163 and 3-12 months in human studies. 153,[164][165][166][167][168][169][170][171][172][173][174][175] The use of TZDs has become less frequent due to higher rates of cardiovascular complications. A recent observational, retrospective, inception cohort of 227,571 Medicare patients who were treated with rosiglitazone or pioglitazone for a 12-month period and followed for up to 3 years after initiation of therapy showed rosiglitazone was associated with a higher risk of cardiovascular complications and all-cause mortality in patients 65 years or older compared with pioglitazone.…”
Section: Emerging Therapeutic Agents For Diabetic Nephropathy Thiazolmentioning
confidence: 99%
“…Their action is performed on b cells through blocking ATP dependent potassium channels [14]. Metformin which is another common anti-diabetic drug lowers hepatic glucose production by decreasing insulin resistance and reducing carbohydrate uptake within intestine, without inducing hyperinsulinemia and hypoglycemia [15][16][17][18][19][20]. Considering that these two drugs are different in their mechanism of action in their way of manipulating insulin levels, we performed this study to compare cognitive impairment among type II diabetic patients treating with metformin with those taking glibenclamide, a drug categorized in sulfonylureas group.…”
Section: Introductionmentioning
confidence: 99%